Reclassification of Bacillus aryabhattai Shivaji et al. 2009 as a later heterotypic synonym of Bacillus megaterium de Bary 1884 (Approved Lists 1980). Issue 22 (8th January 2020) - Narsing Rao, Manik Prabhu; Dong, Zhou-Yan; Liu, Guo-Hong; Li, Li; Xiao, Min; Li, Wen-Jun
ABSTRACT: In the present study, the taxonomic position of Bacillus aryabhattai and Bacillus megaterium was evaluated using morphological, biochemical, phylogenomic and genome analysis. The morphological and biochemical of these two species were almost similar with few exceptions. The major fatty acids in B. megaterium DSM 32 T and B. aryabhattai 21047 T were anteiso-C15:0 and iso-C15:0 . In the phylogenomic tree, both species clade together and shared high 16S rRNA gene sequence similarity (99.6%). The average nucleotide identity values between Bacillus aryabhattai and Bacillus megaterium were above the threshold values for bacterial species delineation. Based upon morphological, biochemical, chemotaxonomic and comparative genome analysis, we propose to reclassify Bacillus aryabhattai Shivaji et al . 2009 as a later heterotypic synonym of Bacillus megaterium de Bary 1884 (Approved Lists 1980). Abstract : Reclassification of Bacillus aryabhattai as a later heterotypic synonym of Bacillus megaterium .